Editor's Note = Note du directeur [17, Spring 1986] - Kealey, Gregory S. (Labour / Le Travail, 1986)
Notes that the journal is celebrating its 10th anniversary and will be hosting two sessions at the annual meeting of the Canadian Historical Association in Winnipeg.

Book Notes [17, Spring 1986] - Palmer, Bryan D.; D.H.A.; Kealey, Gregory S. (Labour / Le Travail, 1986)
The article briefly reviews "Ravished bx the Spirit: Religious Revivals, Baptists, and Henry Alline," by G.A. Rawylk, "The Acadiensis Reader, v. 1: Atlantic Canada Before Confederation and v. 2: Atlantic Canada After Confederation," edited by P.A. Bucknerand David Frank, "The Mysteries of Montreal: Memoirs of a Midwife," by Charlotte Fiihrer, edited by Peter Ward, "The Promoters' City: Building the Industrial Town of Maisonneuve, 1883-I9I8," by Paul-Andre Linteau, translated by Robert Chodos, "Government and Enterprise in Canada," edited by K.J. Rea and Nelson Wiseman, "Collective Bargaining in the Public Service: The Federal Experience in Canada," v. 1-2, edited by Jacob Finkelman and Shirley B. Goldenberg, "The Labor History Reader," edited by Daniel J. Leah, "C. Wright Mills: An American Utopian," by Irving Louis Horowitz, "Foundry Foreman, Foundry men," by Lloyd Zimpel, (San Pedro: Singlejack,1980); "Longshoring on the San Francisco Waterfront," by Reg Theriault, (San Pedro: Singlejack, 1978); and "Night Shift in a Pickle Factory," by Steve Turner (San Pedro: Singlejack, 1980), "The Fight Against Shutdowns: Youngstown's Steel Mill," by Staughton Lynd, "International Labour Reports" (a bimonthly magazine established 1983), "The Idea of Poverty: England in the Early Industrial Age," by Gertrude Himmelfarb, "A History of British Socialism," by Max Beer. with a new introduction by Ken Coates, "English Industrial Cities of the Nineteenth Century," by Richard Dennis, "Shop Floor Bargaining and the State: Historical and Comparative Perspectives," edited by Steven Tolliday and Jonathan Zeitlin, "Wigan Pier Revisited: Poverty and Politics in the 80s," by Beatrix Campbell, " Vision and Method in Historical Sociology," edited by Theda Skoepol, and "Making Sense of Marx," by Joe Elster / reviews by Bryan D. Palmer – "Agriculture in America, 1622-1860," by Andrea J. Tucher / review by D.H.A. – "Labor's Joke Book," edited by Paul Buhle / review by Gregory S. Kealey.

The Character of Class Struggle: Essays in Canadian Working-Class History, 1850-1985 - Palmer, Bryan D.; McKay, Ian; Heron, Craig; Maroney, Heather Jon; Webber, Jeremy; Brandt, Gail Cuthbert; Kealey, Gregory S. (McClelland and Stewart, 1986)
These essays introduce readers to the changing and complex character of class struggle in Canada. Individual essays focus on specific features of Canadian class struggle: regional differences, the role of gender, the character of trade union leadership to the specific nature of conflict in particular industries; and the general features of national periods of upheaval such as the year 1919 and the World War II period. [Of the eight essays, two are original to the volume, while the others are abridged or revised versions of articles that previously appeared in publications such as Labour/Le Travail and New Left Review.] –Publisher's description
Keywords: 19th century; 20th century; Canada; History; Labor disputes; Social conflict; Working class